If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(6y + -5) = 23 + -3(8y + 1) Reorder the terms: 4(-5 + 6y) = 23 + -3(8y + 1) (-5 * 4 + 6y * 4) = 23 + -3(8y + 1) (-20 + 24y) = 23 + -3(8y + 1) Reorder the terms: -20 + 24y = 23 + -3(1 + 8y) -20 + 24y = 23 + (1 * -3 + 8y * -3) -20 + 24y = 23 + (-3 + -24y) Combine like terms: 23 + -3 = 20 -20 + 24y = 20 + -24y Solving -20 + 24y = 20 + -24y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '24y' to each side of the equation. -20 + 24y + 24y = 20 + -24y + 24y Combine like terms: 24y + 24y = 48y -20 + 48y = 20 + -24y + 24y Combine like terms: -24y + 24y = 0 -20 + 48y = 20 + 0 -20 + 48y = 20 Add '20' to each side of the equation. -20 + 20 + 48y = 20 + 20 Combine like terms: -20 + 20 = 0 0 + 48y = 20 + 20 48y = 20 + 20 Combine like terms: 20 + 20 = 40 48y = 40 Divide each side by '48'. y = 0.8333333333 Simplifying y = 0.8333333333
| 6x^2+8x-9.5=0 | | -x+16x-2=0 | | 10/40-20x | | y=x*2-4x-12 | | n+2/3=35 | | 48y^3-3u^4y^3=0 | | 9=u/5-9 | | 7h+31-10=35 | | 7-3m=m-8-4m | | 1-0.05z=0.07 | | 3X+8X-4=14+X+7X | | (5x^4+8x)+(x^4+10)= | | 4(3-7x)-(6-3y)=8-2x | | 4/x+3/x=7 | | 4(3-7y)-(6-3x)=8-2y | | 0=4+5 | | x+2/3+x+3/4=5 | | a+(a+2)+(a/3)=100 | | 3x/63 | | 5m-5m=-10+3-7 | | 3X+3X-4=14+X+7X | | 13x+2=-13(0)+2 | | 6x-(2x+3)=3x-10 | | 4(m-8)=4m | | 2(0.5x-4)=-(x-5) | | 2m+5=5m-35-3m | | 2/(y+2)+(3/y)=(-y)/(y+2) | | K(-5)=6-5+100 | | 2m-9=2m-16+7 | | Y=2x^2-7x-4 | | x/7+2x/9 | | 1/(3x)+(6x-9)/(3x)=(3x-3)/(4x) |